Structural Change and Growth: The Old and the New - Rodrik, Dani; McMillan, Margaret S.; Sepúlveda, Claudia (2017)
Dani Rodrik IFPRI BOOK LAUNCH Structural Change, Fundamentals, and Growth: A Framework and Case Studies Edited by Margaret McMillan, Dani Rodrik, and Claudia Sepúlveda MAY 11, 2017 - 12:15 PM TO 01:45 PM EDT